Histopathological Changes caused by The Chronic Effect of Nitrofurantoin Drug in The Testes of Albino Mice (Baghdad Science Journal, 2015)
The present study was conducted to determine histopathological changes caused by chronic effect of Nitrofurantoin(NFT) in The albino mice Testes. The Study included 40 mice were divided on the five groups: the first group taken distilled water and become control group . the remaining group which are exposure with NFT drug in concentration (100-150-200-250) mg / kg, respectively, Doses were given orally for a period (month and two months). The results of histopathological changes included occurrence of congestion in the blood vessel and degeneration of spermatogonia and aggregation of spermatids in the lumen of semineferous tubules and inhibition of spermatogensis process and decrease of sperm inside the lumen of semineferous tubule as well as necrosis and atrophy within germ cell layer , this changes be greatest in groups with high concentrations (200-250) mg / kg. NFT drug have side effect on testes by inhibition the spermatogenesis process and decrease of mature sperm number and necrosis found within in germ cell layer lining the seminiferous tubules.